HISTORICAL-ENVIRONMENTAL ANALYSIS OF THE BANANAL VILLAGE, LOCATED IN THE INDIGENOUS LAND OF TAUNAY/IPEGUE, USING GEOPROCESSING DATA - Cândido, Aroldo Fialho; Boggione, Giovanni de Araújo (CIPEEX, 2022)
THE PRESENT RESEARCH REFERS TO THE INDIGENOUS PEOPLE OF THE TERENA ETHNIC GROUP, IN THE TRADITIONAL AND HISTORICAL BANANAL VILLAGE, LOCATED IN THE TAUNAY/IPEGUE INDIGENOUS LAND, MUNICIPALITY OF AQUIDAUANA-MS. THE HISTORICAL-ENVIRONMENTAL ASPECTS ARE STUDIED BY CORRELATING THEM WITH SATELLITE IMAGES OF THE REGION, ANALYZING THE POSSIBLE PASSAGE AND TRANSITION OF CUSTOMS OF THE RESIDENTS OF THE TAUNAY/IPEGUE INDIGENOUS LAND, SPECIFICALLY THE BANANAL VILLAGE. THEY REMOTELY MEASURE LOCAL AND ANTHROPIC IMPACTS SUCH AS DEFORESTATION, DEFORESTATION, REFORESTATION, SOIL COVER ANALYSIS, ENVIRONMENTAL MONITORING OR AREAS THAT UNDERGO ALTERATIONS, THOSE ALTERED LANDSCAPES, AMONG OTHER INFORMATION. CURRENTLY, THERE ARE FEW STUDIES USING MONITORING SYSTEMS, REMOTE SENSING REGARDING LAND USE AND LAND COVER IN INDIGENOUS AREAS.